2007
DOI: 10.1007/s00402-007-0393-9
|View full text |Cite
|
Sign up to set email alerts
|

Extremity fracture characteristics in children with impulsive/hyperactive behavior

Abstract: Detecting behavior problems in children admitted with fractures and referring them for treatment, is critical in preventing future serious injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
5
22
1
Order By: Relevance
“…This seems important given that there is evidence to suggest that some children with OI are not socially typical (Uslu & Uslu, 2008). Thus, the findings of the present study, while they require replication, provide evidence that the parenting and peer experiences of children with TBI differs from those who are socially typical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems important given that there is evidence to suggest that some children with OI are not socially typical (Uslu & Uslu, 2008). Thus, the findings of the present study, while they require replication, provide evidence that the parenting and peer experiences of children with TBI differs from those who are socially typical.…”
Section: Discussionmentioning
confidence: 99%
“…Brehaut et al (2003) reported that children with behavioral difficulties were at an increased risk for orthopedic injuries and other studies indicate that children with OI are at higher risk for behavior problems than children from the general child population or those without physical injuries (Goldstrohm & Arffa, 2005; Uslu & Uslu, 2008). Thus, it would be fruitful to examine how parents of children with TBI compare in their parenting practices to parents of socially-typical controls, as well as how parenting moderates the relation between injury group (TBI or socially-typical) and peer social adjustment in the school context.…”
mentioning
confidence: 99%
“…Little has changed in the more than two decades since Davidson's review. Although several additional retrospective chart review and epidemiological population-based studies have shown an association between ADHD and unintentional injuries in children, these studies suffer from many of the limitations noted in Davidson's review (Pastor & Reuben 2006;Bruce et al 2007;Sabuncuoglu 2007;Badger et al 2008;Marcus et al 2008;Uslu & Uslu 2008;Merrill et al 2009). The diagnosis of ADHD in these studies was often not well established; the adequacy of the control groups was uncertain and they relied, for the most part, on parental recall of injuries during a single interview.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of MP use is even higher. 1 Recent studies have shown the prevalence of MP prescriptions to be 7.5% in children aged [6][7][8][9][10][11][12][13][14][15][16][17][18] in Israel, 2 5% in children of the same age group in the United States, and 2.5-4.0% in adults in the United States. 3 Stimulants like MP have been estimated to be abused (used without prescription) in 5-10% of high school students and 5-35% of college students in the United States.…”
mentioning
confidence: 99%